Rare malignant tumors of the ovary during pregnancy: a clinical case report - Shatokhina , Valeriia; Shypko , Sofia; Skuryatina , Nataliia; Synyshyna , Olena (The Ukrainian Scientific Medical Youth Journal, 2023)
This article describes a clinical case of a malignant ovarian neoplasm, which was first detected during an urgent visit of a pregnant woman with signs of fetal distress in the third trimester of pregnancy. The relevance of this problem lies in the possibility of early diagnosis of adnexal tumors during routine ultrasound screenings, the lack of definitive recommendations for the management of such patients and the limited range of treatment methods during pregnancy. The aim of the study is to demonstrate a clinical case of pregnancy with late-detected ovarian malignancy. A 39-year-old pregnant woman at 35 weeks and 4 days’ gestation consulted the antenatal clinic of a city maternity hospital with complaints of a decrease in the number and change in the nature of fetal movements over the past 24 hours. After assessment of the fetal condition (cardiotocography, ultrasound), the woman was hospitalized with a diagnosis: Pregnancy III, 35 weeks and 4 days. Fetal distress in the antenatal period. Fetal growth restriction, stage I. Gestational hypertension without significant proteinuria. Multicompartmental cyst of the right ovary. An urgent cesarean section was performed. Clinical diagnosis: рremature delivery by cesarean section. Medical care for the mother with fetal growth restriction of the first degree, fetal distress in the antenatal period. Cyst of the right ovary. Right-sided adnexectomy. Omental resection. Gestational hypertension. On the 5th day, the patient was discharged in a satisfactory condition with a recommendation for further examination in an oncology hospital. Pathological examination of the right ovary: morphological picture, taking into account the results of immunohistochemical examination, in favor of undifferentiated carcinoma; on repeated viewing - granular cell tumor of the ovary of adult type. The patient was routinely hospitalized at the city oncology center for surgical treatment and further examination. Clinical diagnosis: Bl ovarii gr I, adult-type granulosa cell tumor, T1Nx Mx. Condition after surgical treatment: lower midline laparotomy. Pangisterectomy, omentectomy. Sampling of the retroperitoneal lymph nodes on the right. Sanitation and drainage of the abdominal cavity. Clinical group II. The results of this article are of great practical importance for obstetricians-gynecologists, general surgeons and ultrasound diagnosticians in the differential diagnosis of indirect signs of malignant tumors during pregnancy, in the need to examine all pelvic organs during routine ultrasound screening of pregnant women and in establishing cause and effect relationships in the diagnosis of obstetric complications.